Kepemimpinan Insan Kamil dan Organisasi Pembelajaran - Miftahun Ni'mah Suseno (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2015)
Maintain competitiveness in the global pressure is important for the organization in the face of the ASEAN Community by 2015. Organizations Economy expected to be ready for the change that is so learning organization becomes an important organizational behavior. The leader is a central figure in moving the organization. Figurehead perfect man (Insan Kamil) became one of leadership that are considered capable of responding to global challenges. Insan Kamil Leadership prioritize synergy of brain function (aql) and heart (qalb). The study of brain function in leadership known as neuroleadership, leadership that promotes spiritual function known as the spiritual leadership. This paper psychological perspective view of leadership in Islam (leadership Insan Kamil) that explores human nature as caliph and psychological dynamics of leadership competencies that synergize the brain and heart function in moving the organization as a learning organization. Key words : leadership, insan kamil, learning organization.